Pelatihan Akupresur Untuk Mengurangi Kejadian Disminorhoe Pada Remaja - Liya Lugita Sari; Yesi Putri; Taufianie Rossita (Jurnal Pengabdian Ilmu Kesehatan, 2023)
Menstruation is bleeding that occurs cyclically and occurs in women of reproductive age. Menstruation can be followed by discomfort in the form of dysmenorrhea. Dysmenorrhea is pain in the lower abdomen that extends to the waist, lower back, and thighs. Dysmenorrhea can be reduced by pharmacological and non-pharmacological therapy, namely the acupressure technique. The purpose of this community service is to provide counseling and training to young women at SMAN 05 Manna Bengkulu Selatan. The method of implementing this community service activity is carried out in 3 stages: the planning stage, the activity implementation stage, and the evaluation stage. Before and after counseling and training, a pre-test and post-test were given. The results of this activity revealed an increase in knowledge after young women were counseled and trained on the acupressure technique to reduce dysmenorrhea, with an average p value of 10 at the pretest and 75 at the posttest. After participating in this counseling and training, it is hoped that adolescents will be able to carry out the aqupressure technique independently at home to reduce dysmenorrhea.